Examining the Relation Between Disability Severity Among Older Adults with Disabilities and Sibling Caregiving. (December 2019) - Lee, Chung eun; Burke, Meghan M.; Arnold, Catherine K.
Given the longer lives of individuals with disabilities and the increasing likelihood of siblings fulfilling family caregiving roles, it is critical to identify correlates of sibling caregiving. Yet, little research has examined the relation between the severity of the disability and sibling caregiving. The purpose of this study was to understand the relation between the severity of the disability (defined as functional ability and maladaptive behaviors) and sibling caregiving, including advocacy and future planning. Adult siblings of older individuals with disabilities ( N = 141) completed a national survey. Results indicated that individuals with less functional ability were significantly more likely to receive greater sibling caregiving, advocacy, and future planning. There was a nonlinear relation with respect to sibling caregiving and functional ability with individuals with severe disabilities requiring disproportionately greater sibling caregiving. Furthermore, there was a nonlinear relation between maladaptive behaviors and caregiving demands such that siblings of individuals with the greatest asocial behaviors reported significantly greater caregiving demands.